2018
DOI: 10.1002/aenm.201800758
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Controlling of All‐Inorganic Perovskite at Low Temperature for Efficient Rigid and Flexible Solar Cells

Abstract: organic components with inorganic cations such as cesium (Cs + ) and rubidium (Rb + ) ions can effectively improve the thermal stability. Recently, all-inorganic cesium lead halide perovskites (CsPbX 3 , X = I, Br, Cl, or mixed halides), which have higher melting points (in excess of 460 °C), [10] have been investigated as thermal stable photoabsorption materials. The CsPbI 2 Br perovskites, which possess a reasonable bandgap of 1.9 eV and considerable phase stability, were emphasized as the main research sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 48 publications
4
112
0
2
Order By: Relevance
“…The corresponding periodicity caculated from the XRD patterns is 15.7 Å, which is in accordance with the interlayer distance of (PEA) 2 PbI 4 from previous report . However, the microscopic morphologies of two films are quite different from each other, as illustrated by the cross‐sectional scanning electron microscope (SEM) images in Figure c,d. The crystal grains of hot‐cast film are apparently smaller compared with those of as‐cast film, although the film thickness is ≈ 350 nm for both samples.…”
supporting
confidence: 52%
“…The corresponding periodicity caculated from the XRD patterns is 15.7 Å, which is in accordance with the interlayer distance of (PEA) 2 PbI 4 from previous report . However, the microscopic morphologies of two films are quite different from each other, as illustrated by the cross‐sectional scanning electron microscope (SEM) images in Figure c,d. The crystal grains of hot‐cast film are apparently smaller compared with those of as‐cast film, although the film thickness is ≈ 350 nm for both samples.…”
supporting
confidence: 52%
“…Besides, the facile‐deposited CsPbI 2 Br films exhibit excellent long‐term phase stability and thermal stability. Recently, Rao et al found the as‐deposited non‐perovskite CsPbI 2 Br film rapidly transforms into black cubic phase through a room‐temperature solvent (DMSO) annealing (RTSA) treatment (Figure a) . The solar cells from the room‐temperature‐deposited CsPbI 2 Br film exhibit a maximum PCE of 6.4%, while the efficiency boosts up to 10.4% after the RTSA‐treated CsPbI 2 Br film sintered at low‐temperature of 120 °C.…”
Section: Performance Improvementmentioning
confidence: 99%
“…A photography of the flexible solar cell is given as inset. Reproduced with permission . Copyright 2018, Wiley–VCH.…”
Section: Performance Improvementmentioning
confidence: 99%
“…While flexible electronics have become emerging technologies for various applications such as solar cells, displays, thin‐film transistors, sensors, and power generating window, [ 1–15 ] flexible transparent electrodes need to fulfill the requirements of high transparency, good conductivity, efficient charge transportation to adjacent layers, and robust electrical stability under simultaneously continuous operation bias and mechanical bending. Among various flexible electrodes such as graphene, [ 16,17 ] carbon nanotube, [ 18 ] metallic nanowire, [ 19–21 ] conductive polymer [ 22 ] and their combination, [ 23–25 ] silver nanowire (AgNW)‐based electrode is one of the attractive candidates.…”
Section: Introductionmentioning
confidence: 99%